A new combination in Sagotia (Euphorbiaceae) with an updated key for the genus - Secco, Ricardo De S.; Silva, Otávio Luis Marques Da; Cordeiro, Inês (Phytotaxa, 2019)
A new combination in Sagotia, Sagotia heterocalyx, based on Sandwithia heterocalyx is herein proposed once this taxon shares more similarities with Sagotia (such as flowers without nectaries, the pistillate ones with calyx lobes united only near the base and thick styles, and staminate flowers with sessile to subsessile stamens) than with Sandwithia (whose flowers are provided with nectaries, the pistillate ones with calyx lobes united for more than half of their length and thin styles, and staminate flowers with conspicuous filaments).Comments on morphological affinities between Sandwithia and Sagotia and an updated key for identification of species of these two genera are also presented, along with the lectotypification of Sandwithia guyanensis.